Singly-qualified medical senior house officer in oral and maxillofacial surgery: perspectives from a unit. Issue 5 (June 2016) - Solanki, Kohmal; Bhatti, Nabeel; Bridle, Christopher
Abstract: Despite constituting a minority of senior house officers (SHO) in oral and maxillofacial surgery (OMFS), the number of singly-qualified medical trainees is growing. We describe the experience of a singly qualified medical trainee in OMFS and the unique benefits and opportunities for potential trainees and the department. Overall, the advantages of synergistic training outweigh any deficiencies in knowledge, and in our experience, having both medical and dental trainees in our unit has maximised training opportunities and provided a more holistic approach to patient care. Increased exposure to conditions in the head and neck also benefits trainees who wish to pursue careers in other specialties such as ear, nose, and throat (ENT), neurosurgery, ophthalmology, and plastic surgery.